Bridging the Digital Divide in Disaster Nursing: A Systematic Review of AI and Telehealth Adoption in Low-Resource Settings - Balqis Damanik; Syahferi Anwar; Adewoyin Adejoke Osonuga; Mi Jin Lee (Universitas Muhammadiyah Semarang Press, 2025)
The integration of Artificial Intelligence (AI) and telehealth has significantly transformed disaster response capabil- ities. Nonetheless, a pronounced